PENGUJIAN EFEK PENGHAMBATAN EKSTRAK DAUN WIDURI TERHADAP PERTUMBUHAN LARVA Spodoptera exigua Hubn. (Lepidoptera: Noctuidae) DENGAN MENGGUNAKAN INDEKS PERTUMBUHAN RELATIF - Shahabuddin Shahabuddin; Flora Pasaru (Universitas Tadulako, 2009)
The study was conducted to evaluate the growth inhibition effect of leaf extract ofCrown plant (LEC), Calotropis gigantean, at various concentrations (5%, 4%, 3%, 2 %, 1 %, and 0% )on S. exigua larvae. Inhibition effect was quantified by using growth (GI) and relative growth (RGI)indexes which have some advantages compared to other insect growth parameters. The results showedthat the growth inhibition effect of the leaf extract of C. gigantea could be detected using the GI andRGI. The RGI values decreased with increasing of the extract concentration and the LC50 value ofLEC to S. exigua was about 2.42 %. The results suggested that C. gigantea extracts contain insectgrowth inhibitor substance.Key words: Calotropis gigantea, growth inhibition effect, relative growth index, Spodoptera exigua.